Hydrodynamic and Thermal Analysis of Additively Manufactured Thrust Chamber Cooling Channels - Reynolds, M.; Wunderlin, N.; Snedden, G.; Pitot, J. (The South African Journal of Industrial Engineering, 2025)
The University of KwaZulu-Natal’s Aerospace Systems Research Institute is developing an additively manufactured regeneratively cooled rocket engine and investigating the effects of surface roughness on the hydrodynamic and thermal performance of its cooling channels. Additive manufacturing produces high roughness values, increasing both heat transfer and pressure drop in cooling channels. It is crucial to understand these delicate relationships between pressure drop, heat transfer, and surface roughness. This paper details the strategy and preliminary results of the above investigation. It provides a brief review of the literature associated with surface roughness characterisation, Nusselt number correlations, and friction factor correlations that are relevant to additively manufactured surfaces. In this context, preliminary predictions of thrust chamber temperature and pressure distributions are also presented. Numerical methods, using ANSYS Fluent, are described, and preliminary results are presented and compared with analytical predictions. It was found that the numerical methods predict higher pressure drops and lower heat transfer than those of the analytical methods. Finally, the experimental hardware and procedure that will be used for future cooling channel friction factor measurement is described.